Diseño de un modelo económico con el objetivo de determinar el costo-beneficio del tratamiento de aguas residuales industriales de perforación, en un campo de Ecopetrol S.A. (2016)
The purpose of this investigation was the design of a multivariate economic-mathematical model in order to determine the cost-benefit of treatment of industrial waste water drilling in a field of ECOPETROL S.A. The project was framed in the type of exploratory, descriptive and analytical, it was a fieldwork and secondary information collected.